Contests as Selection Mechanisms: The Impact of Risk Aversion - Christoph March; Marco Sahm (Center for Economic Studies and ifo Institute (CESifo), 2017)
We investigate how individual risk preferences affect the likelihood of selecting the more able contestant within a two-player Tullock contest. Our theoretical model yields two main predictions: First, an increase in the risk aversion of a player worsens her odds unless she already has a sufficiently large advantage. Second, if the prize money is sufficiently large, a less able but less risk averse contestant can achieve an equal or even higher probability of winning than a more able but more risk averse opponent. In a laboratory experiment we confirm both, the non-monotonic impact and the compensating effect of risk aversion on winning probabilities. Our results suggest a novel explanation for the gender gap and the optimality of limited monetary incentives in selection contests.
Keywords: C72; D72; J31; K41; M51; M52; 330; selection contest; risk aversion; competitive balance; gender gap